Memória ferroviária: da mobilização social à política pública de patrimônio - Matos, Lucina Ferreira (2015)
This thesis aims at studying the process of construction and appropriation of the railway past and the transformation of the railway memory as an object of public policy, mainly after the Law n⁰ 11.483/2007. The study approaches the roles played by several social agents, such as the railway preservation associations (APF, Brazilian Portuguese acronym), the Federal Railway (RFFSA, Brazilian Portuguese acronym ) and the National Historical and Artistic Heritage Institute (IPHAN, Brazilian Portuguese acronym), and their resignification and objectification of the railway past, processes that started in the 1970s. The research describes the implementation of the Brazilian railway, in order to contextualize the RFFSA extinction, in 2007, it approaches the APF appearance and evolution and describes the RFFSA work to preserve and protect the railway past through the Railway Historical Heritage Preservation Program (Preserve, Brazilian Portuguese acronym). Finally, the thesis focuses on the work of Iphan, recurring the analysis of the railway property register processes and the study of the consequences of the Law n⁰ 11.483/2007 inside the institution. The movement of valuing the railway past contribute to the debates around the processes of appropriation and patrimonialization of the past.